Smart Water Usage Monitoring Using IoT - Aniq, Zulkarnain Shah (Universiti Malaysia Sarawak (UNIMAS), 2020)
Smart Water Usage Monitoring Using IoT is a system that monitors water usage in domestic households on each different water appliance and activity. The system monitors usage on a daily basis and keeps monthly data for comparison. A mobile application is used as an interface to display water usage and bills estimation. The system uses water flow sensor to detect the volume of water every time water passes through it. Based on the water volume, the bills estimation is calculated according to the local Water Board water rates. Both water usage and bill estimation are sent to Firebase and MySQL database where the mobile application can request the data. A push notification is sent to notify on the usage reaching the threshold.